High pressure single-crystal micro X-ray diffraction analysis with GSE_ADA/RSV software - Dera, Przemyslaw; Zhuravlev, Kirill; Prakapenka, Vitali; Rivers, Mark L.; Finkelstein, Gregory J.; Grubor-Urosevic, Ognjen; Tschauner, Oliver; Clark, Simon M.; Downs, Robert T. (High pressure research, 2013)
GSE_ADA/RSV is a free software package for custom analysis of single-crystal micro X-ray diffraction (SCμXRD) data, developed with particular emphasis on data from samples enclosed in diamond anvil cells and subject to high pressure conditions. The package has been in extensive use at the high pressure beamlines of Advanced Photon Source (APS), Argonne National Laboratory and Advanced Light Source (ALS), Lawrence Berkeley National Laboratory. The software is optimized for processing of wide-rotation images and includes a variety of peak intensity corrections and peak filtering features, which are custom-designed to make processing of high pressure SCμXRD easier and more reliable.